Teachers' self-reported knowledge regarding English learners: perspectives on culturally and linguistically inclusive instruction and intervention. Issue 5 (4th May 2017) - Doran, Patricia Rice
ABSTRACT: Student diversity within U.S. schools has steadily increased in recent years. This trend has driven significant interest, on the part of schools and school systems, in supporting students who are English learners (ELs) and who are culturally diverse. It has also highlighted, for those schools and school systems, the importance of professional development to prepare teachers to support those students effectively. Teacher experience and knowledge regarding this population is particularly important to the cause of inclusive education, as appropriate supports, instruction and inclusion for these learners are highly dependent on teachers' knowledge and skills. This study surveyed teachers in three highly diverse elementary schools with high percentages of ELs, students of minority backgrounds, and students receiving free and reduced-price meals. Results indicated that, despite reporting significant previous professional development on cultural and language diversity, teachers lacked familiarity with basic concepts related to cultural and language diversity and to factors considered in the interventions process for diverse learners. These findings, if replicated, may call into question the efficacy of ongoing professional development efforts and underscore the need for more consistent design, delivery, and evaluation of professional development initiatives or programmes.